Optimalisasi Aplikasi Artificial Intelligence (AI) dalam Pembuatan Media Pembelajaran Inovatif bagi Guru TK ABA Wasur II Kabupaten Merauke - Istiqomah, Nurul; Giovani, Evelin (Jurnal Pengabdian UNDIKMA, 2025)
This community service activity aimed to enhance the knowledge and skills of kindergarten teachers in utilizing AI technology to design innovative teaching media. The method of implementing this community service used training and mentoring with participants, namely ABA Wasur II Kindergarten teachers in Merauke Regency. The stages of the activity included preparation, implementation, application, and monitoring and evaluation. The evaluation was conducted by administering a pre-test and post-test. The results of this community service show that there was an increase in teachers' understanding of AI tools that could be utilized to enhance students’ language skills. Additionally, the teachers were able to effectively apply the AI tools introduced to create teaching media based on the sequence picture method.